Tourism Development Strategy in Girikarto Village, Gunungkidul, Yogyakarta - Utami, Westi (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
The development of tourism, especially on the coast of Gunungkidul, has a significant impact on various aspects of people's lives. This study aims to analyze the socio-economic impact of tourism development and analyze tourism development strategies in Girikarto Village. The research method is descriptive qualitative, mapping the development of tourism potential is based on a SWOT analysis (Strenghtening, Weakness, Opportunity and Threads). Data was collected through observation and in-depth interviews with business actors, pokdarwis, communities, local governments, and village officials. The results of the study show that tourism is able to absorb the workforce of the majority of the community, improve the community's economy, create business opportunities and also change the work pattern of people who previously worked outside the area to return to their home village. Tourism has implications for improving skills, education, and people's lifestyles. In addition to bringing positive impacts, some of the negative impacts of tourism are environmental degradation, reduced vegetation cover, changes in karst morphology, increased congestion, pollution and waste problems. The tourism development strategy can be carried out through optimizing community involvement in tourism (CBT/Community Based Tourism), increasing community capacity and optimizing the role of stakeholders to promote sustainable and equitable tourism for the community and the environment.